Health Benefits of Ganoderma lucidum as a Medicinal Mushroom - Sanem Bulam; Nebahat Şule Üstün; Aysun Pekşen (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Ganoderma lucidum (Curtis) P. Karst., known as “Lingzhi” in China or “Reishi” in Japan, is a well-known medicinal mushroom and traditional Chinese medicine, which has been used for the prevention and treatment of bronchitis, allergies, hepatitis, immunological disorders and cancer. G. lucidum is rarely collected from nature and mostly cultivated on wood logs and sawdust in plastic bags or bottles to meet the demands of international markets. Diverse groups of chemical compounds with pharmacological activities, isolated from the mycelia and fruiting bodies of G. lucidum are triterpenoids, polysaccharides (β-D-glucans), proteins, amino acids, nucleosides, alkaloids, steroids, lactones, lectins, fatty acids, and enzymes. The biologically active compounds as primarily triterpenoids and polysaccharides of G. lucidum have been reported to possess hepatoprotective, antihypertensive, hypocholesterolemic, antihistaminic effects and antioxidant, antitumor, immunomodulatory, and antiangiogenic activities. Several formulations have been developed, patented and used as nutraceuticals, nutriceuticals and pharmaceuticals from G. lucidum’s water or ethanol extracts and rarely purified active compounds. As the result of clinical trials, various products have commercially become available as syrup, injection, tablet, tincture or bolus of powdered medicine and an ingredient or additive in dark chocolate bars and organic fermented medicinal mushroom drink mixes such as green teas, coffees, and hot cacaos. This review has intended to give and discuss recent knowledge on phytochemical and pharmacological compositions, therapeutic and side effects, clinical trials, and commercial products of G. lucidum.